Development of Green Concrete for Mining Roads using Incineration Residue Ash - Lantang, Siswan; Samawi, M. Farid; Tumpu, Miswar (Engineering, Technology & Applied Science Research, 2025)
This study explores the potential of incorporating Incineration Residues Ash (IRA) as a partial replacement for Portland Composite Cement (PCC) in cement production at a mining site in Ceria Indotama Nugraha, Indonesia. Concrete mixtures with different percentages of IRA-0%, 25%, 50%, 75%, and 100%- were evaluated for workability and compressive strength under extreme conditions. The results show that replacing up to 50% PCC with IRA leads to compressive strength values similar to those of traditional concrete (30 MPa), with 25% IRA being the optimal percentage. Additionally, Life Cycle Assessment (LCA) analysis revealed that the environmental impact of concrete can be reduced with IRA replacement, especially regarding CO2 emissions. These findings suggest that using incineration residues in concrete production can be a sustainable and possible alternative for mining road constructions.